2001
DOI: 10.1034/j.1600-0765.2001.360502.x
|View full text |Cite
|
Sign up to set email alerts
|

Chewing sticks: timeless natural toothbrushes for oral cleansing

Abstract: It is generally accepted that oral hygiene maintenance through regular removal of dental plaque and food deposits is an essential factor in the prevention of dental caries and periodontal disease. Methods for oral hygiene vary from country to country and from culture to culture. Despite the widespread use of toothbrushes and toothpastes, natural methods of tooth cleaning using chewing sticks selected and prepared from the twigs, stems or roots from a variety of plant species have been practised for thousands o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
146
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(150 citation statements)
references
References 28 publications
1
146
0
3
Order By: Relevance
“…Instead, herbal chewing sticks taken from plants, shrubs, or trees with high antimicrobial activity (Hobbs 2008) are used for relieving dental problems. Several clinical studies confirmed that chewing sticks, if used appropriately, can be as efficient as toothbrushes in removing dental plaque due to the combined effect of mechanical cleaning, enhanced salivation and leaching-out of antimicrobial substances (Wu et al 2001). The relationship between the pathogenic state and the mode of growth of biofilms has been most clearly established with oral streptococci, which are known to initiate dental caries if they are living in the biofilm environment of dental plaque (Cvitkovitch et al 2003).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Instead, herbal chewing sticks taken from plants, shrubs, or trees with high antimicrobial activity (Hobbs 2008) are used for relieving dental problems. Several clinical studies confirmed that chewing sticks, if used appropriately, can be as efficient as toothbrushes in removing dental plaque due to the combined effect of mechanical cleaning, enhanced salivation and leaching-out of antimicrobial substances (Wu et al 2001). The relationship between the pathogenic state and the mode of growth of biofilms has been most clearly established with oral streptococci, which are known to initiate dental caries if they are living in the biofilm environment of dental plaque (Cvitkovitch et al 2003).…”
Section: Discussionmentioning
confidence: 84%
“…Prevention of dental caries can be achieved through maintaining oral hygiene by regular removal of food deposits and dental plaque, which is traditionally done by non-specific removal by mechanical means (Cowan 1999). Even though toothbrushes and toothpastes have found wide usage, natural methods of teeth-cleaning using chewing sticks selected and prepared from the twigs, stems, or roots from various plant species have been practiced for thousands of years in Asia, Africa, the Middle East, and the Americas (Wu et al 2001). Chewing sticks come from different species of plants and, within one stick, the chemically active component may be heterogeneous (Cowan 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of the modern tooth-brush has its origin in chewing sticks that were used by the Babylonians as early as 3500 BC (Wu CD et al 2001). The toothpaste containing Neem as well as fluoridated toothpaste were equally efficacious against caries-producing bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…34 It is widely distributed in Asia and Africa. 35 The main components are alkaloids like trimethylamine and salvadorine. Chlorides and fluorides are also present in high ratio.…”
Section: Salvadora Persica (Miswak)mentioning
confidence: 99%